Wintering Areas, Migratory Connectivity and Habitat Fidelity of Three Declining Nearctic- Neotropical Migrant Swallows - Imlay Tara Leah (De Gruyter, 2018)
Conservation efforts directed at population declines for migratory animals must consider threats occurring at different stages often separated by vast distances. Furthermore, connectivity between populations and fidelity of individuals to specific habitats during the annual cycle are also important considerations. Avian aerial insectivores are experiencing steep population declines in North America, and those declines may be driven, in part, by conditions on the wintering grounds. Here, using geolocators (2 species; 4 individuals) and stable isotope (δ2H, δ13C and δ15N) measurements of feathers (3 species; 841 individuals), we identified approximate winter areas, and assessed migratory connectivity and among-year winter habitat fidelity for three aerial insectivores (Bank Swallow Riparia riparia, Barn Swallow Hirundo rustica and Cliff Swallow Petrochelidon pyrrhonota) that breed in northeastern North America. All three species of swallows are declining in this region. Our results, largely from the stable isotope analysis, suggest that these species likely winter throughout the Cerrado, La Plata Basin, and the Pampas, in South America. These most likely areas were similar among years (2013-2016) for Bank and Cliff Swallows, but varied for Barn Swallows (2014-2016). We found weak migratory connectivity for all three species, and, with one exception, weak habitat fidelity among years for individuals. For individual Barn Swallows captured in two or more years, we found high repeatability in δ13C values, suggesting some fidelity to similar habitats among years. The most likely wintering areas for these species coincide with large areas of South America experiencing high rates of land-use change.